Simulação numérica de bloco de concreto sobre duas estacas metálicas: influência do comprimento de embutimento e orientação das estacas - De Marchi, Gabriela Souza (Universidade Federal de São Carlos, 2025)
Pile caps are volumetric structures responsible for enabling the transmission of loads from the superstructure to the soil. Among deep foundations, steel piles stand out for their use in engineering works and containment in difficult-to-penetrate soils due to their physical and mechanical properties. Even so, there is a scarcity of specific research and regulations that present sizing methods or experimental results for pile caps. Due to the complexity and high cost of full-size tests considering different analysis variables, it is common to use software based on the finite element method (FEM) to understand the structural behavior of these pile caps. In this context, this research evaluated, through numerical simulation, the influence of the embedded length and orientation of the two steel piles in the capping block, involving the analysis of the structural behavior of these foundation elements. The numerical simulations were initially calibrated based on a geometric and mechanically compatible model with an experimental test, seeking to reproduce the force versus displacement and maximum force curve. It was observed that, when adjusting the variations of the concrete damaged plasticity (CDP) parameters, the viscosity and the mesh discretization significantly influence the structural response, allowing the obtaining of a numerical force versus displacement curve compatible with the experimental results, as well as a maximum load very close to it. In addition, it was found that it is important to consider boundary conditions that faithfully reproduce those applied in the laboratory tests. The results indicated that the orientations of the piles up to 20° did not affect the resistant capacity of the pile cap. However, the orientations of 90°, the embedded length, and the compressive strength of the concrete influenced the ultimate resistance of the element. In addition, the variation in the orientation of the piles influenced how the compressive stresses were dispersed in the pile cap. It was observed that the analytical stress limits were more conservative in the upper nodal zone, presenting lower values in relation to the numerical results. Additional experimental studies are recommended to deepen the understanding of the mechanical behavior of the pile cap on two steel piles.
Numerical simulation of concrete block on two steel piles: influence of embedment length and pile orientation
Keywords: Bloco; Estacas metálicas; Embutimento; Orientação das estacas; Concreto; Projeto; Simulação numérica; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS